Financing of Voluntary Fire Societies in the Republic of Serbia (International Journal of Contemporary Security Studies, 2023)
Voluntary fire societies in the Republic of Serbia are currently a significant operational component and additional assistance to professional fire and rescue units and local emergency headquarters when needed. During the last three decades, this area has been largely neglected and threatened to lead to complete devastation and disappearance of voluntary fire societies in the Republic of Serbia. However, since the adoption of the Law on voluntary firefighting, which was adopted at the end of 2018, the Ministry of the Interior and the Sector for emergency management have started and implemented a series of activities aimed at the systemic development of voluntary firefighting. During this process, significant attention is paid to the financing of voluntary fire societies, which is currently not systematically resolved and this will be the basic hypothesis of the work with the aim that the authors propose the establishment of stable sources of funding that enable smooth operation and functioning of voluntary fire societies. The research in this paper will be focused on the analysis of voluntary firefighting in the countries around the Republic of Serbia and the ways in which they regulated the financing of voluntary fire societies. One of the expected results of the work is the proposal of a financial model aimed at both the national level and the level of local self-governments, which would contribute to further improving the work of voluntary fire societies.